Public transport of firewood across the Mackinac Bridge in Michigan, United States of America: origin, destination, woody taxa, and reasons for transporting firewood. Issue 5 (29th October 2021) - Haack, Robert A.; Petrice, Toby R.
Abstract: Transporting firewood can spread plant pests such as the emerald ash borer, Agrilus planipennis Fairmaire (Coleoptera: Buprestidae), which was discovered in Lower Michigan, United States of America in 2002. In 2005, Michigan banned the transport of hardwood firewood northwards across the Mackinac Bridge, which connects Lower and Upper Michigan. In 2005–2011, 479 drivers of 11 commercial vehicles and 468 private vehicles were interviewed. Firewood was collected in every month of the year, with most firewood collected in June–September. Of the 468 private vehicles surveyed, 400 carried firewood originating from Michigan, 64 carried it from 19 other American states, and four carried it from three Canadian provinces. Most vehicles (93%) were bound for Upper Michigan, 4% were bound for eight other American states, and 3% were bound for four Canadian provinces. Drivers transported 1–275 pieces of firewood, with 33% of drivers having 1–10 pieces and 87% having up to 50 pieces. Surrendered firewood represented 19 tree genera – 18 hardwood genera and one conifer. Of 59 vehicles carrying ash ( Fraxinus ) firewood, 15 had firewood with A. planipennis signs. Firewood was transported mainly for camping (76%), for weight (15%), and to be used at cottages (5%).